2020
DOI: 10.1021/acs.bioconjchem.9b00804
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescent Antibodies through Photoconjugation of Protein G–Luciferase Fusion Proteins

Abstract: Bioluminescent antibodies represent attractive detection agents in both bioanalytical assays and imaging. Currently, their preparation relies on genetic fusion of luciferases to antibodies or nonspecific chemical conjugation strategies. Here, we report a generic method to generate well-defined covalent antibody− luciferase conjugates starting from commercially available monoclonal antibodies. Our approach uses fusion proteins consisting of the bright blue light-emitting luciferase NanoLuc (NL) and an Fcbinding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…To overcome the problem, several original approaches were developed. So, the bioorthogonal conjugation or photoconjugation methods of obtaining luciferase-antibody conjugates that would provide a high conjugate yield, control over conjugation site and stoichiometry, and retention of the luciferase activity were elaborated [ 108 , 109 ]. However, the analytical application of luciferases in most cases is based on the bioluminescence of their derivatives extended with biospecific polypeptides obtained by genetic fusing.…”
Section: Ctz-dependent Luciferase Analytical Applicationmentioning
confidence: 99%
See 2 more Smart Citations
“…To overcome the problem, several original approaches were developed. So, the bioorthogonal conjugation or photoconjugation methods of obtaining luciferase-antibody conjugates that would provide a high conjugate yield, control over conjugation site and stoichiometry, and retention of the luciferase activity were elaborated [ 108 , 109 ]. However, the analytical application of luciferases in most cases is based on the bioluminescence of their derivatives extended with biospecific polypeptides obtained by genetic fusing.…”
Section: Ctz-dependent Luciferase Analytical Applicationmentioning
confidence: 99%
“…Wouters et al reported an easily accessible, efficient, and chemoselective method for the synthesis of antibody-luciferase conjugates. [ 109 ]. The NanoLuc was genetically fused with protein G domain containing the photo-cross-linkable non-natural amino acid para-benzoylphenylalanine (developed by Hui et al [ 223 ]) that can be photo-cross-linked to the antibody using UV light illumination (365 nm).…”
Section: Ctz-dependent Luciferase Analytical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pET28a(+) vectors containing DNA encoding for Gx-SB, Gx-LB, mNG-NL and SUMO-TNFα-SB were ordered from GenScript. The sequence of mNG-NL was reported by Suzuki et al 32 , and a His-tag at the N-terminus and a Strep-tag at the C-terminus were included to facilitate purification 26 . Site-directed mutagenesis to change SB sequences was carried out using the QuikChange Lightning Site-Directed Mutagenesis kit (Agilent technologies) and specifically designed primers.…”
Section: Cloningmentioning
confidence: 99%
“…Although methods for the generation of antibody-split luciferase fusion proteins are available, they are based on non-specific conjugation or cumbersome recombinant expression of antibody fusions 13,24 . RAPPID does not require additional protein engineering and uses protein G-mediated photoconjugation to generate well-defined antibody conjugates directly from commercially available antibodies 25,26 . Additionally, we introduce a green light-emitting calibrator luciferase as a simple method to provide a robust blue-over-green ratiometric readout and direct internal calibration.…”
Section: Introductionmentioning
confidence: 99%